Cepheid pulsations resolved by interferometry. Issue 69 (10th September 2015) - Nardetto, N.; Kervella, P.
Abstract : The very high spatial resolution provided by current interferometers (VLTI, CHARA, …) makes it possible to measure directly the change in angular diameter of more than thirty Cepheids over their pulsation cycle. When combined with radial velocity measurements, this allows us to measure precisely their distances in a quasi-geometrical way. This is an essential information to calibrate the Cepheid's Period-Luminosity law. On the other hand, a careful analysis of the dynamical structure of their atmosphere is required to avoid biases in their distance determination.